2014
DOI: 10.1017/s003118201400122x
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Sarcocystis fusiformis sarcocysts from the water buffalo (Bubalus bubalis)

Abstract: S U M M A R YFour valid species of Sarcocystis have been reported from the water buffalo (Bubalus bubalis): Sarcocystis fusiformis, Sarcocystis buffalonis, Sarcocystis levinei and Sarcocystis dubeyi. Here, we redescribe structure of S. fusiformis sarcocysts by scanning and transmission electron microscopy (SEM, TEM). Twenty-one macroscopic sarcocysts from oesophagus of the water buffalo in Egypt were examined by light microscopy, SEM and TEM. The sarcocyst wall was up to 9 μm thick, depending on the section an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Thus, the fine structure of the sarcocysts has been reported in several papers (Ghaffar et al 1978; Kan and Dissanaike 1978;Tongson and Molina 1979;Zaman et al 1980;Parairo et al 1988;Dubey et al 1989b;Jehle et al 2009;Abu-Elwafa et al 2015;Dubey et al 2015), and S. fusiformis was among the first Sarcocystis spp. to have its complete life cycle elucidated, when it was shown that domestic cats acted as definitive hosts (Dissanaike et al 1977a, b;Scholtyseck and Hilali 1978).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, the fine structure of the sarcocysts has been reported in several papers (Ghaffar et al 1978; Kan and Dissanaike 1978;Tongson and Molina 1979;Zaman et al 1980;Parairo et al 1988;Dubey et al 1989b;Jehle et al 2009;Abu-Elwafa et al 2015;Dubey et al 2015), and S. fusiformis was among the first Sarcocystis spp. to have its complete life cycle elucidated, when it was shown that domestic cats acted as definitive hosts (Dissanaike et al 1977a, b;Scholtyseck and Hilali 1978).…”
Section: Introductionmentioning
confidence: 82%
“…Hence, they seemed to have been amplified from DNA belonging to S. fusiformis, which presumably also predominated in the templates. The aberrant sequences could possibly have represented non-functional copies of the genes originating from slightly degenerate DNA in dead or dying merozoites in the central portion of the large sarcocysts, which is known to contain few intact merozoites (Manuel et al 1983;Dubey et al 2015). If so, they may constitute a very small fraction of the total number of copies of the genes present in the DNA templates and may therefore not be detected by direct sequencing of PCR products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formalin-fixed tissues were embedded in paraffin, sectioned 5 µm thick and stained with hematoxylin and eosin (H and E). After examination of the H and E sections, cysts canditates for electron microscopy were excised with the help of an scalpel and processed as described by Dubey et al (2015b). rRNA (~925 bp), and ITS-1 (~900 bp) were excised and purified using QIAquick Gel Extraction (Qiagen, Inc., Valencia, CA).…”
Section: Light (Lm) and Transmission Electron (Tem) Microscopymentioning
confidence: 99%
“…Fresh muscles were examined for sarcocysts presence by squeezing; individual cysts were excised and kept frozen until molecular assays. Five cysts detected in the HE sections of deer #14183 were excised and processed for transmission electron microscopy (TEM) as reported by Dubey et al (2015b).…”
Section: Microscopical Examinationmentioning
confidence: 99%